The outcomes of nutritional therapy in patients with non-alcoholic fatty liver disease (NAFLD): pitfalls in getting fit from fat - Shaikh, Sabhita Shabir; Afnan, Badder Hina; Nasim, Sumaira; Ahmed Farooqi, Waqas; Darbari, Ahsan Ali; shabbir, alveena (Journal of the Pakistan Medical Association, 2024)
Objectives: To evaluate the outcomes of nutritional intervention on non-alcoholic fatty liver disease parameters, and to determine the reasons for non-compliance with nutritional therapy. Method: The interventional study was conducted from May 2020 to October 2022 at the National Institute of Liver and Gastrointestinal diseases, Dow University Hospital, Ojha Campus, Karachi, and comprised patients of either gender aged 18-65 years who had been diagnosed with non-alcoholic fatty liver disease based on abdominal ultrasound. Anthropometrics, physical activity level, and biochemical markers were evaluated at baseline and 6 months after the intervention that involved nutritional assessment, counselling and guidance related to dietary modification and optimisation of physical activity level. The effect of the intervention was evaluated by improvement in liver enzymes, biochemical parameters, anthropometric indices and any change in the level of physical activity. The reasons for noncompliance were also recorded. Data was analysed using SPSS 22. Results: Out of 118 subjects enrolled, 61(51.69%) completed the study. Most patients were females 81(68.6%), married 25(21.2%) and housewives 64(54.2%). There were 16(26.2%) subjects who had 3-10kg weight reduction. The reduction in serum cholesterol and triglyceride levels was not significant (p>0.05). Also, no significant change was observed in the level of physical activity compared to the baseline (p>0.05). Overall, 27(44.3%) patients showed compliance with treatment. The main reasons for noncompliance were lack of time 21(34.4) and knee joint pain 5(8.2%). Conclusion: Lifestyle modification can be beneficial for weight-loss in the management of non-alcoholic fatty liver disease. However, awareness of its importance and willingness in initiating real-life practical steps with subsequent adherence to dietary therapy was found lacking in the sample studied. Key Words: Fatty liver, Non-alcoholic steatohepatitis, Diet therapy, Nutrition, Physical activity.